Improvising techniques in experimental physics for Nigerian schools: a compound microscope (2007)
In the course of formal education, Nigeria faces some major problems, one of these is the lack of teaching material which should go a long way to stimulate learning. It is for this purpose that a compound microscope has been designed and constructed for use in Nigerian secondary schools where such equipment is either completely lacking or available in limited quantity. A compound microscope consists essentially of a base, a stage, an arm and two tubes which support the objective and the eye-piece lenses. The magnifying power of the constructed microscope was dertermined and found to be 10. The experimental and the theoretical magnifying powers differed by 8.5%. The constructed microscope can be used in physical and biological lessons.